1994
DOI: 10.1111/j.1745-4573.1994.tb00524.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Nitrogenous Compounds in Freshwater Crayfish (Procambarus Clarkii) Tail Meat Stored in Ice

Abstract: Changes in the protein and nonprotein nitrogen (NPN) fractions in the tail meat of freshwater crayfish (Procambarus clarkii) were monitored during ice storage. In addition, the accumulation of nonprotein nitrogenous compounds was estimated and compared with sensory evaluation. The myofibrillar fraction, expressed as a percentage of total nitrogen, did not vary during this study while the NPN, sarcoplasmic and stroma protein fractions changed during the first week of storage. SDS‐PAGE patterns of the sarcoplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…1998). A steep pH increment indicates accumulation of alkaline metabolites such as TMA and TVB because of increased bacterial activity (Flick et al. 1994; Huss 1996).…”
Section: Resultsmentioning
confidence: 99%
“…1998). A steep pH increment indicates accumulation of alkaline metabolites such as TMA and TVB because of increased bacterial activity (Flick et al. 1994; Huss 1996).…”
Section: Resultsmentioning
confidence: 99%
“…Riaz and Qadri (1985), evaluating quality changes in lobster muscle ( Panulirus poliphagus ) stored on ice, reported that increments during storage lower than or equal to 0.1 pH units represented a first‐quality muscle. Pronounced pH increase indicates the accumulation of alkaline metabolites from bacterial accumulation over time (Flick et al. 1994; Huss 1995).…”
Section: Resultsmentioning
confidence: 99%
“…Endogenous proteolytic activity may be another factor related with alteration of pH in sea products. Final pH 7 in control samples at 15 days suggests a quality loss of fish muscles, according to several authors who reported that a significant increase in pH indicates a loss in the freshness of fish muscle (Flick et al, 1994;Huss, 1996;Castillo-Yáñez et al, 2007).…”
Section: Resultsmentioning
confidence: 99%